2008
DOI: 10.1016/j.ijpara.2007.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Giardia duodenalis assemblage A and E infections in calves

Abstract: A molecular epidemiological study was conducted on 100 dairy (499 calves) and 50 beef (333 calves) farms in Belgium to estimate the prevalence of different Giardia duodenalis assemblages in calves younger than 10 weeks of age. Positive samples from the epidemiological study and from a previous clinical study were selected and genotyped based on the amplification of the b-giardin gene. To investigate the occurence of mixed assemblage A and E infections in calves, a novel assemblage-specific PCR was developed ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
5
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 28 publications
10
98
5
3
Order By: Relevance
“…First, they can be used to get a better estimate of the occurrence of mixed infections in clinical samples, which is likely to be strongly underestimated. Indeed, using tpi assemblage-specific primers in a standard PCR protocol, it has been shown that 31% of the calf isolates can be identified as mixed assemblage A and E infections (13), and a similar proportion of mixed A and B infections was found in human and monkey isolates using the same approach (14,22). Here, by applying the more sensitive qPCR assays, we have shown that an even larger percentage of human stool samples (37 to 83%, depending on the sensitivities of the different assays) contained DNAs of both assemblages A and B.…”
Section: Discussionmentioning
confidence: 99%
“…First, they can be used to get a better estimate of the occurrence of mixed infections in clinical samples, which is likely to be strongly underestimated. Indeed, using tpi assemblage-specific primers in a standard PCR protocol, it has been shown that 31% of the calf isolates can be identified as mixed assemblage A and E infections (13), and a similar proportion of mixed A and B infections was found in human and monkey isolates using the same approach (14,22). Here, by applying the more sensitive qPCR assays, we have shown that an even larger percentage of human stool samples (37 to 83%, depending on the sensitivities of the different assays) contained DNAs of both assemblages A and B.…”
Section: Discussionmentioning
confidence: 99%
“…All samples were typed at the triose phosphate isomerase (tpi) locus using assemblage A, B and E specific primers as previously described (Sulaiman et al 2003;Geurden et al 2008;Levecke et al 2009). A representative subset of samples were also amplified using a nested PCR and sequenced at the glutamate dehydrogenase (gdh) locus (n = 30) as described by Read et al (2004) and at the tpi (n = 27) locus using the assemblage-specific primers described above.…”
Section: Molecular Typingmentioning
confidence: 99%
“…The primary 186 PCR was performed as described by Sulaiman et al, (2003). For the second round 187 reaction, assemblage-specific primers and conditions for assemblage A (product ~332bp) 188 and E (product ~388bp) were used as previously described (Geurden et al, 2008; (2009), with PCR reaction mixtures described in an earlier study (Sweeny et al, 2011b). …”
Section: Pcr Amplification 167mentioning
confidence: 99%